Fractionally integrated processes of Ornstein-Uhlenbeck type - Valdivieso Serrano, Luis Hilmar (Pro Mathematica, 2007)
An estimation methodology to deal with fractionally integrated processes of Ornstein- Uhlenbeck type is proposed. The methodology is based on the continuous Whittle contrast. A simulation study is performed by driving this process with a symmetric CGMY background Lévy process.